2022
DOI: 10.2147/phmt.s323812
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Impacts of Diabetes Mellitus on Umbilical Cord During Pregnancy

Abstract: As a feto-maternal connection route, the umbilical cord is an important determinant of fetal well-being. The umbilical vessels, unlike major vessels, are not fed by the vasa vasorum, making them more vulnerable to hemodynamic changes induced by maternal diseases such as diabetes mellitus. Furthermore, it may be discarded for exacerbating any perinatal illness. The umbilical cord is the major supporter of a successful neonatal prognosis, since it is the sole organ that initiates life. It plays the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Six 14 , 31 , 33 , 34 , 35 , 36 studies reported on MCA, with only 3 studies allowing for a 2 × 2 table construction. 30 , 33 , 35 As shown in Figure 4 and Appendix 5 , assessed adverse outcomes were composite adverse outcome, preterm birth, cesarean delivery for fetal distress, hypertensive disorder, 5-minute APGAR score <7, acidemia, NICU admission, respiratory distress, jaundice, hypoglycemia, and neonatal death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six 14 , 31 , 33 , 34 , 35 , 36 studies reported on MCA, with only 3 studies allowing for a 2 × 2 table construction. 30 , 33 , 35 As shown in Figure 4 and Appendix 5 , assessed adverse outcomes were composite adverse outcome, preterm birth, cesarean delivery for fetal distress, hypertensive disorder, 5-minute APGAR score <7, acidemia, NICU admission, respiratory distress, jaundice, hypoglycemia, and neonatal death.…”
Section: Resultsmentioning
confidence: 99%
“…The first is an increase in vasoconstriction and placental blood volume within the UA, exacerbating vessel resistance and thus producing a high PI. 8 , 13 , 14 The second is termed the “brain-sparing effect,” in which the MCA vasodilates in an attempt to redirect blood flow to the brain and other vital organs, resulting in reduced vascular resistance and a lower PI. 8 , 15 , 16…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with gestational diabetes mellitus show a down-regulation of vascular endothelial growth factor A (VEGFA), which has a critical role in angiogenesis, producing an abnormal coiling pattern of the umbilical cord [67]. Histopathologic changes have also been described such as a discontinuous endothelial cell of the intima, extravasation of arterial blood to Wharton's jelly, thinner vein wall, and larger lumen [68]. Also, hypo-coiling has been described as one of the main abnormal patterns of coiling in gestational diabetes [69].…”
Section: Umbilical Cord Alterations Related To Non-hypertensive Mater...mentioning
confidence: 99%
“…The extent and specifics of how pathological factors influence the progression of pregnancy and its outcomes largely rely on the preservation of compensatory and adaptive mechanisms within the utero-fetoplacental system. The functional parameters of this system determine the level of disruption in fetal condition [1][2][3][4][5]. Abnormalities in the structure and location of the umbilical cord are associated with intrauterine distress, asphyxia, stillbirth, increased risk of congenital malformations, fetal aneuploidy, intrauterine growth restriction, and complications such as gestational diabetes and preeclampsia [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%